1999
DOI: 10.1093/molehr/5.2.96
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of epidermal growth factor and transforming growth factor alpha on aromatase activity in granulosa cells from polycystic ovaries

Abstract: We investigated aromatization and the mechanism of action of epidermal growth factor (EGF) and transforming growth factor alpha (TGFalpha) on oestradiol biosynthesis in freshly prepared granulosa cells from polycystic ovaries. Freshly prepared granulosa cells from polycystic ovaries incubated for only 3 h under basal conditions secreted significantly (P< 0.001) greater amounts of oestradiol-17beta than that of granulosa cells from normal ovaries. 8-Bromo-cyclic adenosine monophosphate (8-Br-cAMP), but not foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Exposure of granulosa cells to EGF/TGF␣ promotes cell proliferation [26] associated with a loss of differentiated function, exemplified by a marked reduction in E 2 production in vitro [27][28][29][30] and in vivo [31]. Theca cells have been identified as a key site of TGF␣ expression in the bovine ovary and evidence suggests that TGF␣ of thecal origin exerts a local paracrine action on neighboring granulosa cells to modulate their proliferation and responsiveness to gonadotropins and other regulatory factors [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of granulosa cells to EGF/TGF␣ promotes cell proliferation [26] associated with a loss of differentiated function, exemplified by a marked reduction in E 2 production in vitro [27][28][29][30] and in vivo [31]. Theca cells have been identified as a key site of TGF␣ expression in the bovine ovary and evidence suggests that TGF␣ of thecal origin exerts a local paracrine action on neighboring granulosa cells to modulate their proliferation and responsiveness to gonadotropins and other regulatory factors [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…In cumulus cells, EGF promotes Ca 2+ efflux and improves their expansion during maturation (Hill et al ., 1999; O'Donnell et al ., 2004). It was furthermore reported that EGF stimulates granulosa cells proliferation in vitro (pig: May et al ., 1992) and estrogen production through aromatase activation (human: Misajon et al ., 1999; goat: Behl & Pandey, 2001). There is evidence for EGF regulating the in vitro cellular activities of granulosa cells either by inhibiting LH receptor production (Hattori et al ., 1995) or inhibin secretion (Serta & Seibel, 1993) or by stimulating FSH receptor expression (Luciano et al ., 1994) and binding affinity (May et al ., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…EGF also promotes in vitro proliferation of porcine granulosa cells obtained from preantral follicles (Morbeck et al ., 1993) and growth of early follicles in cow (Gutierrez et al ., 2000), hamster (Roy, 1993), mouse (Boland & Gosden, 1994) and human (Roy & Kole, 1998). In antral follicles, EGF has been shown to stimulate in vitro oocyte maturation (mouse: Smitz et al ., 1998; De La Fuente et al ., 1999; sheep: Guler et al ., 2000; cattle: Lonergan et al ., 1996; human: Goud et al ., 1998; pig: Prochazka et al ., 2003; Li et al ., 2002), cumulus cells expansion (mouse: O'Donnell et al ., 2004), granulosa cell proliferation (pig: May et al ., 1992) and estrogen production (human: Misajon et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%